Innovative Approach to Enhance Bioavailability of Birch Bark Extracts: Novel Method of Oleogel Development Contrasted with Other Dispersed Systems - Laura Andze; Sanita Vitolina; Rudolfs Berzins; Janis Rizikovs; Daniela Godina; Arturs Teresko; Solveiga Grinberga; Eduards Sevostjanovs; Helena Cirule; Edgars Liepinsh; Aigars Paze (Plants, 2024)
Birch outer bark extract (BBE), containing pentacyclic triterpenes such as betulin, lupeol, and betulinic acid, is a widely recognized natural product renowned for its diverse pharmacological effects. However, its limited water solubility restricts its bioavailability. Therefore, the main objective is to enhance the bioavailability of BBE for pharmaceutical use. In this study, we aimed to develop a dispersion system utilizing a unique oleogel-producing method through the recrystallization of BBE from an ethanol solution in the oil phase. We generated an oleogel that demonstrates a notable 42–80-fold improvement in betulin and lupeol peroral bioavailability from BBE in Wistar rats, respectively. A physical paste-like BBE hydrogel developed with antisolvent precipitation showed a 16–56-fold increase in the bioavailability of betulin and lupeol from BBE in rat blood plasma, respectively. We also observed that the repeated administration of the BBE oleogel did not exhibit any toxicity at the tested dose (38.5 mg/kg betulin, 5.2 mg/kg lupeol, 1.5 mg/kg betulinic acid daily for 7 days). Betulin and betulinic acid were not detected in rat heart, liver, kidney, or brain tissues after the peroral administration of the oleogel daily for 7 days. Lupeol was found in rat heart, liver, and kidney tissues.